ANALISIS VARIASI ARUS-WAKTU TABUNG (mAs) DAN ITERATIVE RECONSTRUCTION (IR) DENGAN PENGUKURAN MODULATION TRANSFER FUNCTION (MTF) PADA CITRA CT SCAN KEPALA - Irsal, Muhammad; Zikri, Ikhwan; Sutoro, Shinta Gunawati; Winarno, Guntur; Mullah, Ikra; Akhridinata, Dinda (Prodi Fisika FST UNJA, 2025)
To optimize head CT examination protocols, tube current-time (mAs) variation and the use of iterative reconstruction (IR) are often combined to decrease radiation dose to patients, which may have an impact on image quality and radiation dose. Modulation transfer function (MTF) is an objective measurement to determine the spatial resolution of CT images, so it is expected to provide information on ideal optimization parameters considering radiation dose and image quality. The research method is quantitative descriptive type, data collection was carried out at one of the hospitals in Padang in the August-December period of 2024. Then CT imaging was performed using a head CT protocol that was exposed to the phantom daily CT QC with variations in tube-current of 200 mAs, 300 mAs and a combination of IR with iDose and without iDose. The analysis was performed on 10 pieces of head CT images which will then calculate the 50% MTF value using imageJ. After that, the results of the study will be carried out by making a graph of the average value and a comprehensive literature review is carried out to analyze the tube current-time variation with MTF measurements on head CT images. The results showed that the MTF values of the time-current tube and IR variations tended to have the same pattern for all, so that in this study it can be said that variations in tube current-time (mAs) and iterative reconstruction (IR) cannot affect MTF.